MADURA LITERATURE AS A MEDIUM FOR LEARNING MADURESE IN THE GLOBALIZATION ERA - Laili Amalia; Tjitra Ramadhani; Yuliarsih Yuliarsih (Universitas Labuhanbatu, 2023)
This study aims to describe the application of Madurese literature as a medium for learning Madurese in the globalization era Qualitative descriptive research method with research subjects of fourth grade students at SDIT Multazam Pamekasan. The research location is SDIT Mulatazam Pamekasan which is located in Buddih Village, Pademawu District, Pamekasan Regency. Data collection through interviews, observation and questionnaires. The results of the research and discussion of the children's literature used are the Madurese song poetry entitled Kembang Malate and tondhu' majheng. With the application of this Madurese children's literary work, students' Madurese vocabulary and language skills develop rapidly. Students find it easy to pronounce and understand the meaning of the Madurese language if it is conveyed in the form of songs that have a happy tone because it is different from everyday language, the language in literary works is emo-aesthetic in nature which expresses beauty. Because language in literature is a language that is creative, for example there is sound play in poetry and rhymes, by reading literary works intensely, students are increasingly creative in using their language. Students become trained to operate grammatical structures better and creatively. Students also know the level of language contained in Madurese and its proper use. Students are now starting to actively use Madurese, especially when communicating with peers.Key Word: Madura literature, Madurese, globalization era AbstrakPenelitian ini bertujuan untuk mendeskripsikan penerapan sastra Madura sebagai media pembelajaran bahasa Madura di era globalisasi. Metode penelitian deskripstif kualitatif dengan subjek penelitian siswa kelas IV SDIT Multazam Pamekasan. Lokasi penelitian adalah SDIT Mulatazam Pamekasan yang terletak di Desa Buddih Kecamatan Pademawu Kabupaten Pamekasan. Pengumpulan data melalui wawancara, observasi dan angket. Diperoleh hasil penelitian dan pembahasan karya sastra anak yang digunakan adalah puisi lagu Madura yang berjudul Kembang Malate dan tondhuâ€™ majheng. Dengan penerapan karya sastra anak Madura ini, kemampuan kosakata dan bahasa Madura siswa berkembang pesat. Siswa merasa mudah melafalkan dan memahami makna bahasa Madura jika disampaikan dalam bentuk lagu yang bernada riang gembira sebab berbeda dengan bahasa keseharian, bahasa pada karya sastra bersifat emotis-estetis yang mengekspresikan keindahan. Karena bahasa dalam sastra adalah bahasa yang sifatnya kreatif, misal ada permainan bunyi pada puisi dan pantun, maka dengan membaca intens karya sastra, siswa semakin kretaif penggunaan bahasanya. Siswa menjadi terlatih mengoperasikan struktur gramatika dengan lebih baik dan kreatif.Â Siswa juga mengetahui tingkatan bahasa yang terdapat dalam bahasa Madura serta penggunaannya dengan tepat. Siswa kini mulai aktif menggunakan Bahasa Madura terutama ketika berkomunikasi bersama teman sebaya.Kata kunci: Sastra Madura, Bahasa Madura, era globalisasi